Hybrids to the rescue [hybrid electric vehicles]. - Jones, W.D (IEEE spectrum)
Whilst pure electric vehicles have floundered, hybrid electric vehicles (HEVs) have been making major gains and could soon make their mark. This article discusses the failings of pure electric vehicles and how HEVs get round the problems. The development and introduction of HEVs is briefly mentioned. The tax incentives for buying HEVs in Japan are discussed and the situation in the USA outlined.